Immunotherapy for colorectal cancer - Yu, Bing; Kang, Jian; Lei, Hong; Li, Zhe; Yang, Hao; Zhang, Meng (Frontiers in Immunology, 2024)
Colorectal cancer is the third most common cancer and the second most lethal cancer in the world. The main cause of the disease is due to dietary and behavioral factors. The treatment of this complex disease is mainly based on traditional treatments, including surgery, radiotherapy, and chemotherapy. Due to its high prevalence and high morbidity, more effective treatments with fewer side effects are urgently needed. In recent years, immunotherapy has become a potential therapeutic alternative and one of the fastest-developing treatments. Immunotherapy inhibits tumor growth by activating or enhancing the immune system to recognize and attack cancer cells. This review presents the latest immunotherapies for immune checkpoint inhibitors, cell therapy, tumor-infiltrating lymphocytes, and oncolytic viruses. Some of these have shown promising results in clinical trials and are used in clinical treatment.